Targeting Angiogenesis with Multitargeted Tyrosine Kinase Inhibitors in the Treatment of Non-Small Cell Lung Cancer - Giorgio V. Scagliotti; Ramaswamy Govindan (2010)
Abstract It has been >35 years since the link between angiogenesis and the growth of tumors was first reported. Targeting angiogenesis became feasible with the availability of bevacizumab, an anti–vascular endothelial growth factor monoclonal antibody. Initial studies revealed that the combination of bevacizumab and chemotherapy led to longer overall survival times than with chemotherapy alone in patients with advanced colorectal cancer. Since then, drug development strategies have added small molecule tyrosine kinase inhibitors to the panel of antiangiogenic agents under evaluation; data from numerous trials are now available. The challenge now is to identify the optimal antiangiogenic agent for specific patient groups and to understand not only the mechanistic differences between agents, but also the variability in their antitumor activity across different tumor types and their differing side-effect profiles. As in other solid tumors, angiogenesis contributes to the development of non-small cell lung cancer (NSCLC), and this review summarizes the role of angiogenesis in this disease. We review the current developmental status of antiangiogenic tyrosine kinase inhibitors (including vandetanib, sunitinib, axitinib, sorafenib, vatalanib, and pazopanib) in NSCLC and conclude by briefly discussing the need for optimal patient selection and potential future directions.